A STUDY ON DEVELOPMENT OF REFINED EMPIRICAL FORMULATION IN PREDICTING THE ULTIMATE STRENGTH OF STIFFENED PANEL SUBJECTED TO LONGITUDINAL COMPRESSION - LIM, HUI LING (2019)
Stiffened panels are one of the main structural components in ships and ship-shaped offshore structures with unstiffened panel elements